Reproductive Morbidity among Tribal and Non-tribal Women in India: A Special Focus to Domestic Violence - Sogarwal, Ruchi; Dwivedi, Laxmi Kant (Journal of Population and Social Studies [JPSS], 2008)
The objective of this study is to identify the prevalence as well as the determinants of gynecological morbidity and the treatment seeking behaviour of tribal and non-tribal women in Madhya Pradesh. An attempt has been made in this paper to examine whether domestic violence against women would have any influence on their health problems. The present study is based on NFHS-2 (1998-99) data and it is estimated from women’s self reported experience. Logistic regression analyses are used to assess the net effect of socio-demographic covariates on the probability of reporting on symptoms of gynecological morbidity. Apart from this, for better understanding of the effects of the covariates under study, the predicted percent of women reporting any gynecological health problems is presented. The result shows that the prevalence of women having at least one gynecological problem is highest in non-tribal (47 percent) with the most common symptoms being abdominal pain, itching and burning sensation while urination. However, in spite of high prevalence of gynecological problems large proportions of such women do not seek any advice or treatment for these problems. The percent of women reporting any reproductive health problems among the tribal women who are working, have children two to four, age is 20-24 years, have low autonomy, never experienced pregnancy wastage, were currently not using contraceptives and ever experienced any violence is around 43 percent. The results of the study stress the need for greater attention to the quality of care in reproductive health programmes in connection with gynecological morbidity. The findings suggest the need for treatment at health facilities in tribal and non-tribal population of Madhya Pradesh.